Coherent structural trapping through wave packet dispersion during photoinduced spin state switching - Henrik T. Lemke (Nature Portfolio, 2017)
Ultrafast nonadiabatic chemical dynamics during molecular photo-transformations remain challenging to describe since electronic/nuclear configurations are coupled. Here the authors use time-resolved X-ray absorption spectroscopy to probe the light-induced spin-state trapping dynamics of [Fe(bpy)3]2+beyond the Born-Oppenheimer approximation.